Synoptic Conditions of Droughts and Dry Winds in the Black Sea Steppe Province Under Recent Decades - Semenova, Inna; Slizhe, Mariia (Frontiers in Earth Science, 2020)
The features of regional atmosphere circulation, which are accompanied simultaneously by two high impact hydrometeorological phenomena (such as droughts and dry winds) in the Black Sea Steppe zone of Ukraine were considered. Dry wind as a complex phenomenon is widespread throughout Ukraine during the warm season of the year. Dry winds often accompany a drought, but they appear as peripheral processes in contrast to the droughts, which are usually formed in the central parts of anticyclones. The number of days with dry winds at the Steppe stations varies on average from 10 to 20 cases to 40–50 cases per warm season, while in the coastal zone the number of days decreases sharply due to a common increase of air atmospheric relative humidity. Analysis of the interannual dynamics of dry winds showed that the number of days with dry winds increases significantly in seasons characterized by a high aridity, according to values of the drought index used. Two time intervals with high and low frequency of seasonal droughts and dry winds were detected during the considered period: 1995–2015. These phenomena have become more intense after 2004, compared to the previous decade. Backward trajectories of air particles showed that the most cases of dry winds originate in air masses, which form up to 5 days previously at the surface level to the east or north-east outside of the territory of Ukraine and then pass into the study area within 5 days.